The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2147/jpr.s119851
|View full text |Cite
|
Sign up to set email alerts
|

Are patients' and doctors' accounts of the first specialist consultation for chronic back pain in agreement?

Abstract: IntroductionThe first consultation at a specialist pain clinic is potentially a pivotal event in a patient’s pain history, affecting treatment adherence and engagement with longer term self-management. What doctors communicate to patients about their chronic pain and how patients interpret doctors’ messages and explanations in pain consultations are under-investigated, particularly in specialist care. Yet, patients value personalized information about their pain problem.Patients and methodsSixteen patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…We included 69 studies (figure 1), 24 with clinicians (n=630), 32 with patients (n=1072) 14 44-74 13 with mixed samples of patients and clinicians (n=45) (table 1). [75][76][77][78][79][80][81][82][83][84][85][86][87] Detailed characteristics of included studies can be found in online supplementary table S2. Table 2 shows the results of the critical appraisal of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…We included 69 studies (figure 1), 24 with clinicians (n=630), 32 with patients (n=1072) 14 44-74 13 with mixed samples of patients and clinicians (n=45) (table 1). [75][76][77][78][79][80][81][82][83][84][85][86][87] Detailed characteristics of included studies can be found in online supplementary table S2. Table 2 shows the results of the critical appraisal of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Considering their long relationships with medical clinics and pain management centres, it is quite possible that patients' interactions with the therapeutic team and experiences is represented in how they receive and respond to therapeutic interventions, and that in turn affects treatment outcomes. It is likely that patients' expectations differ from what is offered in clinics [6] although neither party may be aware of this [7]. Establishing a trusting relationship with the healthcare team involved may be an important part of treatment, [8,9] particularly for patient self-management.…”
Section: Introductionmentioning
confidence: 99%
“…This mixed methods study evaluated an aspect of physiotherapist‐patient interaction that previously has not been studied in detail. The initial hypothesis, derived from existing literature (Barker et al, 2009; Darlow et al, 2013, 2015; White et al, 2016) and clinical experience, was that there would be inconsistencies between what the therapist thinks she/he tells the patient and what the patient actually remembers. This hypothesis was not confirmed for the first item of advice that was given (100% concordance); however, for second, and especially for the third item of advice this was more the case (92 and 67% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption and confidence may be mistaken as the literature shows inconsistencies between physiotherapists' self‐assessment and patients' perception (Miller, 2008; Peek, Carey, Mackenzie, & Sanson‐Fisher, 2018), and problems in communication between patients and physiotherapists and other healthcare professionals (Barker, Reid, & Minns Lowe, 2009; Darlow et al, 2013, 2015; Gulbrandsen, Madsen, Benth, & Laerum, 2010). Patients do not always understand the proposed outcome of the recommended intervention, along with the time frame of the plan of care (White, Lee, & Williams, 2016). Physiotherapists have been found to dominate communication, which has been found to be dependent on the clinician, and only partly individualized to the specific patient (Roberts & Bucksey, 2007; Street, Gordon, Ward, Krupat, & Kravitz, 2005), with the absence of individualized information likely to diminish treatment effectiveness (Lucassen & Olesen, 2016).…”
Section: Introductionmentioning
confidence: 99%